Durability Performance of Fiber-Reinforced Metakaolin-Based and Red Mud-Fly Ash-Slag-Activated Geopolymers with Recycled Aggregates - Yilmaz, Arin; Ergun, Seckin; Uysal, Mucteba; Dilbas, Hasan; Aygormez, Yurdakul; Canpolat, Orhan (SPRINGER HEIDELBERG, 2023)
In the concept of green geopolymer, a good start would be if all/many of the geopolymer components were made from recycled materials. In this research, high recycled material consumption was aimed for forming a geopolymer. Binder materials were selected as 40% metakaolin, 20% fly ash, 20% granulated ground furnace slag, and 20% red mud, and, also the aggregates were selected as recycled material (50% recycled aggregate powder and 50% marble powder). In addition, different types of fibers (brass-coated steel fiber, polyamide fiber and polypropylene fiber) at different ratios (0-0.25-0.50-0.75-1.00%) were used. Compressive strength, bending strength, ultrasound pulse velocity were obtained in the tests and nonlinear fracture parameters such as initial fracture toughness and unstable fracture toughness were determined by equations. Besides, the durability properties (abrasion resistance, high-temperature (up to 600 & DEG;C) resistance, freeze-thaw (up to 300 cycles) resistance, and sodium/magnesium sulfate attack) of the best geopolymers were considered and the best series for each fiber type was determined by a decision support system. According to the test results, the bending strength was improved by curing age and all types of fibers. Besides, the first crack and unstable crack propagation are delayed by fibers. 0.75% polypropylene fiber with a high curing time (up to 56 days) can be proposed for higher performance of geopolymer. In addition, consideration of a decision support system eases finding the best solution among the huge experimental data and gives better results instead of the conventional singular evaluation approach.
Keywords: Geopolymer; Metakaolin; Recycled powder; Fiber; Short-term; Long-term; QUASI-BRITTLE FRACTURE; DOUBLE-K CRITERION; MECHANICAL-PROPERTIES; COMPRESSIVE STRENGTH; CRACK-PROPAGATION; CONCRETE; MICROSTRUCTURE; STEEL; PARAMETERS; WASTE; Science & Technology - Other Topics